Experimental Study on the Mechanical Response and Seepage Characteristics of Low-Permeability Reservoirs under Pressure-Driven Water Injection Conditions - Wang, Mengqi (Academic Journal of Management Science and Engineering, 2026)
To address the issues of insufficient injection capacity and slow energy replenishment associated with conventional waterflooding development in low-permeability oil reservoirs, this study takes typical low-permeability core samples from the X block in the eastern Yin’e Basin as the research subject. A systematic series of experiments on rock mechanics, single-phase and two-phase seepage, and imbibition is carried out to reveal the mechanical response of the reservoir, the evolution of seepage capacity, and the redistribution characteristics of residual oil under pressure-driven water injection conditions. The results indicate that pressure-driven water injection can significantly improve pore-throat connectivity and flow pathways, thereby enhancing the co-permeability of oil and water phases. In addition, imbibition oil displacement facilitates further mobilization of residual oil in medium and large pores.